2015
DOI: 10.15376/biores.10.2.2823-2835
|View full text |Cite
|
Sign up to set email alerts
|

Bamboo (Bambusa vulgaris Schrad.) from Moist Forest and Derived Savanna Locations in South West Nigeria – Properties and Gluability

Abstract: Bamboo culms of Bambusa vulgaris Schrad. were collected from two locations in moist forests and two sites in derived Savanna zones in South West Nigeria. The study involved chemical analyses, density variability, bonding tests, gluability tests, and measurements of bending strength of the bamboo in addition to durability testing with decay fungi and treatability of glued boards with a copper-based wood preservative. Chemical analyses showed a uniform composition of the bamboo with a cellulose content of 45 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 6 publications
1
12
1
Order By: Relevance
“…Anokye et al (2016) reported the basic density of bamboo material to be in the range of 0,4 to 0,9 g/cm 3 . Ogunsanwo et al (2015) also reported an average density value of 666,8 kg/m 3 for Bambusa vulgaris samples taken from the moist forest zone of Nigeria. The value obtained in this study is similar to the study of Ogunsanwo et al (2015), but less by 0,49 %.…”
Section: Densitymentioning
confidence: 91%
See 4 more Smart Citations
“…Anokye et al (2016) reported the basic density of bamboo material to be in the range of 0,4 to 0,9 g/cm 3 . Ogunsanwo et al (2015) also reported an average density value of 666,8 kg/m 3 for Bambusa vulgaris samples taken from the moist forest zone of Nigeria. The value obtained in this study is similar to the study of Ogunsanwo et al (2015), but less by 0,49 %.…”
Section: Densitymentioning
confidence: 91%
“…Ogunsanwo et al (2015) also reported an average density value of 666,8 kg/m 3 for Bambusa vulgaris samples taken from the moist forest zone of Nigeria. The value obtained in this study is similar to the study of Ogunsanwo et al (2015), but less by 0,49 %. Despite the change in the density of the samples, statistical analysis showed no significant difference in the mean density of the samples as shown in Table 1.…”
Section: Densitymentioning
confidence: 91%
See 3 more Smart Citations